2020
DOI: 10.1136/thoraxjnl-2019-214457
|View full text |Cite
|
Sign up to set email alerts
|

Association between COPD exacerbations and lung function decline during maintenance therapy

Abstract: BackgroundLittle is known about the impact of exacerbations on COPD progression or whether inhaled corticosteroid (ICS) use and blood eosinophil count (BEC) affect progression. We aimed to assess this in a prospective observational study.MethodsThe study population included patients with mild to moderate COPD, aged ≥35 years, with a smoking history, who were followed up for ≥3 years from first to last spirometry recording using two large UK electronic medical record databases: Clinical Practice Research Datali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 27 publications
2
49
0
1
Order By: Relevance
“… 49 Real-life data also showed that elevated BEC was associated with better outcomes for those on triple therapy (vs dual bronchodilator therapy), 50 and in frequent exacerbators is associated with more rapid lung function decline. 12 Higher BEC (ie, >200 cells/µL) may also be a predictor of OCS success in those experiencing exacerbations, 51 and eosinophil guided therapy has been shown to reduce OCS exposure in patients admitted to hospital with acute exacerbation of COPD. 52 Taken together, these results suggest the value of BEC to tailor treatments to specific COPD phenotypes and endotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 Real-life data also showed that elevated BEC was associated with better outcomes for those on triple therapy (vs dual bronchodilator therapy), 50 and in frequent exacerbators is associated with more rapid lung function decline. 12 Higher BEC (ie, >200 cells/µL) may also be a predictor of OCS success in those experiencing exacerbations, 51 and eosinophil guided therapy has been shown to reduce OCS exposure in patients admitted to hospital with acute exacerbation of COPD. 52 Taken together, these results suggest the value of BEC to tailor treatments to specific COPD phenotypes and endotypes.…”
Section: Resultsmentioning
confidence: 99%
“… 9 This is important since interventions such as smoking cessation and pulmonary rehabilitation 10 , 11 may improve prognosis and drugs such as inhaled corticosteroids (ICS) may improve current symptoms and exacerbations that are associated with rapid lung function loss. 12 Furthermore, patients who experience a greater exacerbation burden after initiation of maintenance therapy have worse lung function at diagnosis and a more rapid lung function decline thereafter, emphasizing the need for better treatment strategies. 13 These findings highlight the importance of earlier intervention among patients with COPD, to more proactively diagnose and manage optimally.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the proportion of patients with a blood eosinophil count ≥ 300/µl was 24.3% and ICS was used by 14.6% (25), while the proportion with a blood eosinophil count ≥ 300/µl was 21.2% and ICS was used by 42.9% in our study. Importantly, in patients with COPD with a high blood eosinophil count, the use of ICS was reported to signi cantly reduce the rate of lung function decline, while FEV 1 decline was more rapid in patients not treated with ICS (18). Additionally, a low blood eosinophil pro le is related with a high bacterial burden (26) and emphysema progression (27).…”
Section: Discussionmentioning
confidence: 99%
“…Besides demographic risk factors, including a higher age, a lower body mass index (BMI), being a current smoker, and more severe dyspnea (11,14), frequent or acute exacerbation events are important risk factors for the rapid decline in lung function (15)(16)(17). Recent studies indicate that acute exacerbation and a rapid decline in FEV 1 are related with high counts of blood eosinophils (18). However, few researchers report the relative decline of lung function (percentage change from baseline FEV 1 per year [%/year]), rather reporting the absolute decline in lung function (FEV 1 ml per year [ml/year]).…”
Section: Introductionmentioning
confidence: 99%
“…In COPD patients, higher B‐Eos levels are associated with an improved response to ICS in preventing exacerbations 13–16 . During exacerbations, higher B‐Eos levels predict greater response to oral corticosteroids, while lower levels are associated with worse outcomes 17,18 . Furthermore, exacerbations are associated with an increased decline in lung function among COPD patients with elevated B‐Eos and without ICS 18 .…”
Section: Introductionmentioning
confidence: 99%